24-h Movement Guidelines and Overweight and Obesity Indicators in Toddlers, Children and Adolescents: A Systematic Review and Meta-Analysis - Marques, Adilson (2023)
Background Engaging in physical activity increases energy expenditure, reducing total body fat. Time spent in sedentary behaviours is associated with overweight and obesity, and adequate sleep duration is associated with improved body composition. This systematic review aimed to analyse the relationship between compliance with the 24-h movement guidelines and obesity indicators in toddlers, children and adolescents. Methods A systematic review and meta-analysis was conducted. PubMed, Web of Science and Scopus were searched from inception to December 2021. Cross-sectional and prospective studies that analysed the relationship between 24-h movement guidelines and overweight and obesity written in English, French, Portuguese or Spanish were included. PROSPERO registration number is CRD42022298316. Results The associations between meeting the 24-h movement guidelines and standardised body mass index were null in the two studies for toddlers. Seven studies analysed the relationship between compliance with the 24-h movement guidelines and overweight and obesity among preschool children. Of these seven studies, six found no association between compliance with 24-h movement guidelines and body composition. Among children and adolescents, 15 articles were analysed. Of these 15 studies, in seven, it was found that children and adolescents who meet the 24-h movement guidelines were more likely to have lower risks of overweight and obesity. The metaanalysis yielded a pooled OR = 0.80 (95% CI = 0.68 to 0.95, p = 0.012, I2 = 70.5%) in favour of compliant participants. Regarding participants’ age groups, compliance with 24-h movement guidelines seems to exert greater benefits on overweight and obesity indicators among children-adolescents (OR = 0.62, p = 0.008) compared to participants at preschool (OR = 1.00, p = 0.931) and toddlers (OR = 0.91, p = 0.853). Conclusion Most included studies have not observed a significant relationship between compliance with the 24-h movement guidelines and overweight and obesity in toddlers, children and adolescents.